Structural, optical and mechanical properties of thin diamond and silicon carbide layers grown by low pressure microwave linear antenna plasma enhanced chemical vapour deposition - Taylor, Andrew; Drahokoupil, Jan; Fekete, Ladislav; Klimša, Ladislav; Kopeček, Jaromír; Purkrt, Adam; Remeš, Zdeněk; Čtvrtlík, Radim; Tomáštík, Jan; Frank, Otakar; Janíček, Petr; Mistrík, Jan; et al. (My University, 2016)
In this work, we detail the properties of thin silicon carbide and polycrystalline diamond layers grown by microwave plasma enhanced chemical vapour deposition with linear antenna delivery. Structural, mechanical and optical properties are compared for their potential use as transparent hard coatings. Silicon carbide layers exhibit mechanical properties comparable to thin diamond layers but with a signiﬁcantly higher adhesion and lower optical absorption coefﬁcient over a wide spectral range.
Strukturální, optické a mechanické vlastnosti tenkých diamantových vrstev a tenkých vrstev karbidu křemíku deponovaných mikrovlnnou plasmou podpořenou chemickou plynnou depozicí s rozvodem lineární anténou za nízkého tlaku
Keywords: Diamond; Silicon carbide; Adherence; Mechanical properties; Optical properties; diamant; karbid křemíku; adheze; mechanické vlastnosti; optické vlastnosti